2021
DOI: 10.3389/fchem.2021.679967
|View full text |Cite
|
Sign up to set email alerts
|

Eco-Friendly Synthesis, Biological Evaluation, and In Silico Molecular Docking Approach of Some New Quinoline Derivatives as Potential Antioxidant and Antibacterial Agents

Abstract: A new series of quinoline derivatives 5–12 were efficiently synthesized via one-pot multicomponent reaction (MCR) of resorcinol, aromatic aldehydes, β-ketoesters, and aliphatic/aromatic amines under solvent-free conditions. All products were obtained in excellent yields, pure at low-cost processing, and short time. The structures of all compounds were characterized by means of spectral and elemental analyses. In addition, all the synthesized compounds 5–12 were in vitro screened for their antioxidant and antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…In an effort to elucidate the plausible mechanism by which these new synthesized chromenol, dihydroquinoline, and thiopyran compounds could exhibit their antimicrobial activity, in the present study, in silico molecular docking studies ( Abdelmonsef et al, 2021 ; Abo-Bakr et al, 2021 ) on bacterial target enzyme UDP-N-acetylmuramatel-alanine ligase (MurC) (PDB ID: 2F00) and Human lanosterol 14α-demethylase (PDB ID: 6UEZ) were performed to demonstrate the mechanism of antibacterial and antifungal activity, and to get insights regarding the binding affinity and the intermolecular interactions of the newly synthesized compounds with the active sites of the target enzymes ( Abdelmonsef et al, 2016 ; HA and SP, 2016 ; Dasari et al, 2017 ; Rondla et al, 2017 ; Haredi Abdelmonsef, 2019 ; Abdelmonsef and Mosallam, 2020 ; El-Maghraby and Abdelmonsef, 2020 ; El-Naggar et al, 2020 ; Haredi Abdelmonsef et al, 2020 ; Noser et al, 2020 ; Rashdan et al, 2020 ; El-Saghier et al, 2021 ; Sobhi et al, 2021 ). Ampicillin was used as a standard drug for in silico screening of the newly synthesized compounds.…”
Section: Resultsmentioning
confidence: 99%
“…In an effort to elucidate the plausible mechanism by which these new synthesized chromenol, dihydroquinoline, and thiopyran compounds could exhibit their antimicrobial activity, in the present study, in silico molecular docking studies ( Abdelmonsef et al, 2021 ; Abo-Bakr et al, 2021 ) on bacterial target enzyme UDP-N-acetylmuramatel-alanine ligase (MurC) (PDB ID: 2F00) and Human lanosterol 14α-demethylase (PDB ID: 6UEZ) were performed to demonstrate the mechanism of antibacterial and antifungal activity, and to get insights regarding the binding affinity and the intermolecular interactions of the newly synthesized compounds with the active sites of the target enzymes ( Abdelmonsef et al, 2016 ; HA and SP, 2016 ; Dasari et al, 2017 ; Rondla et al, 2017 ; Haredi Abdelmonsef, 2019 ; Abdelmonsef and Mosallam, 2020 ; El-Maghraby and Abdelmonsef, 2020 ; El-Naggar et al, 2020 ; Haredi Abdelmonsef et al, 2020 ; Noser et al, 2020 ; Rashdan et al, 2020 ; El-Saghier et al, 2021 ; Sobhi et al, 2021 ). Ampicillin was used as a standard drug for in silico screening of the newly synthesized compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, guanosine has been reported as a potent antibacterial activity both in vitro and in vivo [ 43 ]. Moreover, in silico molecular docking and modeling techniques [ 44 , 45 ] were performed in the current study for the ethanolic extracted compound (guanosine) for better understanding their mode of action through the interaction with the active site pockets of PBP1 and PBP3, and to identify new inhibitors as antibacterial agents. The result showed that the target compounds exhibited binding energy higher than standard drug imipenem (−7.1 and −8.1 Å, respectively) against the target proteins ( Table 4 ; Figure 5 , Figure 6 and Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…In silico molecular docking studies [42] were performed for all compounds using molecular docking in the PyRx tool, to explore and explain the orientation of molecules bound in the active sites of the target enzymes. The eighteen molecules showed good binding energy, indicating that they were successfully docked to the active site of the target enzymes HK and NADH [43]. Figure 1 and Figure 2 represent the molecular interactions between the best docked All synthesized compounds 3-20 were characterized by spectroscopic techniques, such as FT-IR and NMR spectroscopy, and elemental analysis as shown in the Supplementary Materials.…”
Section: In Silico Docking Studymentioning
confidence: 99%